Tropes of Fear: the Impact of Globalization on Batek Religious Landscapes - Tacey, Ivan (Religions, 2013)
The Batek are a forest and forest-fringe dwelling population numbering around 1,500 located in Peninsular Malaysia. Most Batek groups were mobile forest-dwelling foragers and collectors until the recent past. The Batek imbue the forest with religious significance that they inscribe onto the landscape through movement, everyday activities, storytelling, trancing and shamanic journeying. However, as processes of globalization transform Malaysian landscapes, many Batek groups have been deterritorialized and relocated to the forest fringes where they are often pressured into converting to world religions, particularly Islam. Batek religious beliefs and practices have been re-shaped by their increasing encounters with global flows of ideologies, technologies, objects, capital and people, as landscapes are opened up to development. This article analyzes the ways these encounters are incorporated into the fabric of the Batek’s religious world and how new objects and ideas have been figuratively and literally assimilated into their taboo systems and cosmology. Particular attention is paid to the impacts of globalization as expressed through tropes of fear.